Parents' Effort to Avoid Bullying among early Age Children - Sherly Utami, Winda; Zubaidah, Zubaidah; Utami, Rahmi Dwi (Journal of Islamic Early Childhood Education, 2023)
Bullying is a problem that becomes the center of attention in early childhood. To minimize the occurrence of bullying, parents need to participate in handling bullying so that it doesn't happen to children. This research uses the method of literature study or literature study. the data obtained by researchers comes from research results, books, and existing data, then the results and literature are described or reviewed again. Based on a review of literature studies, it shows that parental involvement is very important in dealing with bullying. The important thing that parents need to do in dealing with bullying behavior is to pay attention to children's feelings, invite children to communicate so that children have the courage to say what they want to say. Parents participate in taking action against bullies and encourage children who are more prone to bullying to interact more actively and remind their peers to help them do well.